Efficacy of Wolbachia-mediated sterility to reduce the incidence of dengue: a synthetic control study in Singapore - Lim, Jue Tao (2024)
Background: Due to the absence of available therapeutics and good vaccines, vector control solutions are needed to mitigate the spread of dengue. Matings between male Aedes aegypti mosquitoes infected with the wAlbB strain of Wolbachia and wildtype females yield non-viable eggs. We evaluated the efficacy of releasing wAlbB-infected A aegypti male mosquitoes to suppress dengue incidence. Methods: In this synthetic control study, we conducted large-scale field trials in Singapore involving release of wAlbB-infected A aegypti male mosquitoes for dengue control via vector population suppression, from epidemiological week (EW) 27, 2018, to EW 26, 2022. We selected two large towns (Yishun and Tampines) to adopt an expanding release strategy and two smaller towns (Bukit Batok and Choa Chu Kang) to adopt a targeted-release approach. Releases were conducted two times a week in high-rise public housing estates. All intervention and control locations practised the same baseline dengue control protocol. The main outcome was weekly dengue incidence rate caused by any dengue virus serotype. We used incidence data collected by the Singapore Ministry of Health to assess the efficacy of the interventions. To compare interventions, we used the synthetic control method to generate appropriate counterfactuals for the intervention towns using a weighted combination of 30 control towns between EW 1, 2014 and EW 26, 2022. Findings: Our study comprised an at-risk population of 607 872 individuals living in intervention sites and 3 894 544 individuals living in control sites. Interventions demonstrated up to 77·28% (121/156, 95% CI 75·81–78·58) intervention efficacy despite incomplete coverage across all towns until EW 26, 2022. Intervention efficacies increased as release coverage increased across all intervention sites. Releases led to 2242 (95% CI 2092–2391) fewer cases per 100 000 people in intervention sites during the study period. Secondary analysis showed that these intervention effects were replicated across all age groups and both sexes for intervention sites. Interpretation: Our results demonstrated the potential of Wolbachia-mediated incompatible insect technique for strengthening dengue control in tropical cities, where dengue burden is the greatest.